2014
DOI: 10.1117/12.2073538
|View full text |Cite
|
Sign up to set email alerts
|

Packaged FBG sensors for real-time stress monitoring on deep-water riser

Abstract: The safety of under-water risers in drilling platform is of great significance. A packaged fiber Bragg grating (FBG) sensor for real-time stress monitoring is designed for the applications on oil drilling risers under 3000 meters deep water. A copper tube which is the main component of the sensor has a small hole along its axes and a groove at its each end. The bare FBG is passed through the small hole and fixed to its ends by epoxy resin. Then the copper tube is packaged by filling the groove with structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The five wavelength curves have downward trends on October 15 when the risers were in laying conditions, and upward trends on 30 November 2014 when risers were in recovery conditions. The previous experimental investigations in the lab [ 22 ] indicated that the wavelength values of FBG sensors are proportional to temperature changes and inversely proportional to water pressure changes. According to the trends of temperature and pressure under seawater in riser working conditions, the downtrends and the uptrends of the curves are consistent with the actual shifts of measured wavelengths.…”
Section: Data and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The five wavelength curves have downward trends on October 15 when the risers were in laying conditions, and upward trends on 30 November 2014 when risers were in recovery conditions. The previous experimental investigations in the lab [ 22 ] indicated that the wavelength values of FBG sensors are proportional to temperature changes and inversely proportional to water pressure changes. According to the trends of temperature and pressure under seawater in riser working conditions, the downtrends and the uptrends of the curves are consistent with the actual shifts of measured wavelengths.…”
Section: Data and Analysismentioning
confidence: 99%
“…In this paper, after applying an all-metal packaging technology [ 22 ], a new bundle-structure sensor for riser stress monitoring was developed to overcome these problems. In cooperation with several departments of the China National Offshore Oil Corporation (CNOOC), a marine test of the sensor was completed on the “hysy-981” ocean oil drilling platform in a sea area of south china sea named Lingshui, which is near the city of Sanya.…”
Section: Introductionmentioning
confidence: 99%